Quality Control of Glehniae Radix, the Root of Glehnia Littoralis Fr. Schmidt ex Miq., Along its Value Chains - Chen, Yuan; Lei, Lujing; Bi, Yaqiong; Jiang, Linlin; Guo, Wenfang; Wang, Jianhua; Li, Minhui (Frontiers in Pharmacology, 2021)
Glehniae Radix (GR) is one of the major medicinal materials in China. The global demand for GR, especially in Asian countries, is constantly increasing, and the supply of wild medicinal materials falls short of the demand. Previous studies have shown that the production and processing modes of different value chains (VCs) impact the quality of medicinal materials. After 4 years of field and market research, this study includes interviews with stakeholders in the VCs, integrates different types of VCs, and further analyzes the VCs. GR characteristics were also assessed; the length and upper-middle diameter of the collected samples were measured, and the effective components of the samples were determined to rank the GR samples according to their quality. The effective components were further analyzed by the K-means clustering method. Concomitantly, the local price (the sales price of the place where the medicinal materials are produced) and market price (the sale price of medicinal materials in the market) of GR in Chifeng, Inner Mongolia, and Anguo, Hebei, were documented, and the ARIMA (Autoregressive Integrated Moving Average) method was used to predict the GR price. Ten VCs are summarized in this article. The results showed that the income of the staff at the beginning of the VC is inadequate. Regarding GR origin, Inner Mongolia GR showed higher quality than that of other areas. As a result, the price of medicinal materials is relatively high, which corresponds to the market price of the survey. The forecast results showed that the market price of GR would increase slightly in the future, which could provide reference for the selection of medicinal materials cultivation in the future. Through the study, it was found that the vertical integration in the VCs of GR could guarantee not only the benefit of the growers but also the traceability of the medicinal materials, which further guarantees the quality of the medicinal materials. However, the complex relationship between the cultivation area and the quality of the medicinal materials is not clear, which should be addressed in future research.